Fibrolytic enzymes in ruminant nutrition and their effect on forage cell wall integrity - Van de Vyver, Wilhelmus Francois Joubert (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD(Agric))--Stellenbosch University, 2011.